The Effect of Digital Payment and Self Control on Students' Impulse Behavior in Palopo City - Artika Sari Devi; Suhardi M Anwar; A. Antong (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study aims to understand the influence of ease of transactions using digital payments on consumer behavior. The study examined the impulsive behavior of students in Palopo City, both directly and in the aquarium, with internal factors such as self-control. This study used a quantitative approach with a descriptive research type. Data analysis used multiple linear regression analysis. The results of this study indicate that digital payments have a significant effect on impulsive behavior, but self-control has a positive effect on impulsive behavior among students in Palopo City. This indicates that the higher a person's self-control, the lower their impulsive behavior.